Hak Ex Officio Hakim dalam Menetapkan Kewajiban Suami Terhadap Isteri dalam Perkara Cerai Talak - Setiawan, Danie (University Of Bengkulu Law Journal, 2022)
Judges in carrying out their duties in court must uphold justice, because justice is the main foundation for the purpose of law. In the practice of civil procedural law within the Religious Courts, judges due to their position or ex officio can decide a case more than what is demanded, even though the parties in the case are not prosecuted. This right is fully within the authority of judges in deciding cases so that the values ​​of legal certainty, justice and benefit are realized. ex officio rights, a judge can decide things that are not stated in the prosecution, for example charging a living, iddah wife to the ex-husband after the divorce. This ex officio right aims to be able to defend rights that are usually not fulfilled by an ex-husband. Husbands, who are supposed to give rights to their wives as organizers of all daily household needs, often ignore their responsibilities. It is intended that the wife has the rights that must be received even after the divorce by considering the situation on the part of the wife and the husband's ability to accept these obligations. By using a normative juridical methodology, namely facing legal problems by looking at the legal rules from the prevailing laws and regulations. So that the results of this study show that judges in carrying out their duties in divorce cases can use ex officio in giving consideration to decisions on husband's obligations towards his wife.